Music 2.0 and artistic research. Beyond a thousand years of Western art music - Assis, Paulo de (2023)
Arguing that society is going through a major civilisational transformation and claiming that Western art music has been a one thousand year-long epochal phenomenon, this paper is a plea for a reconfiguration of musical practices, provocatively labelled as ‘Music 2.0’. This reconfiguration can benefit from ongoing developments in artistic research, crucially moving from an aesthetic regime of the arts to more pluralistic, inclusive, and diverse aesthetico-epistemic modes of expression.
FRIS
1
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music; Assemblage